John Anthony Berry, "Yves Congar’s Vision of Faith", Pontificia Università Gregoriana, Roma 2019, ss. 409 - Roszak, Piotr (Warszawskie Studia Teologiczne, 2020)
The article reviews the book: John Anthony Berry, "Yves Congar's Vision of Faith", Pontificia Università Gregoriana, Roma 2019, pp. 409.